1994
DOI: 10.1007/bf00005667
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and conservation of blackwater fishes in Peninsular Malaysia, particularly in the North Selangor peat swamp forest

Abstract: One of the most extreme freshwater habitats in Peninsular Malaysia is the peat swamp forest, with dark-coloured and highly acidic waters. Surprisingly, little is known about blackwater fishes in Peninsular Malaysia. Until 1968, only 26 fish species were known from blackwaters throughout Peninsular Malaysia, of which only one can be regarded as stenotopic. A recent intensive survey of part of the North Selangor peat swamp forest yielded 47 species, of which 14 are probably stenotopic taxa. These include four un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 7 publications
0
45
0
5
Order By: Relevance
“…Past logging of the Selangor forest has not adversely aVected the Wsh fauna signiWcantly (Ng et al 1994), but recent extension and deepening of drains may have signiWcant impacts. A large number of the Wsh species seem to be generally fairly resistant to perturbations, being able to survive in irrigation canals and roadside ditches containing water draining from the peat swamps, but when the peat swamps are completely destroyed, the Wsh vanish (Ng et al 1994).…”
Section: Fishmentioning
confidence: 98%
See 2 more Smart Citations
“…Past logging of the Selangor forest has not adversely aVected the Wsh fauna signiWcantly (Ng et al 1994), but recent extension and deepening of drains may have signiWcant impacts. A large number of the Wsh species seem to be generally fairly resistant to perturbations, being able to survive in irrigation canals and roadside ditches containing water draining from the peat swamps, but when the peat swamps are completely destroyed, the Wsh vanish (Ng et al 1994).…”
Section: Fishmentioning
confidence: 98%
“…A total of 200-300 Wsh species are recorded from the peat swamps of Peninsular Malaysia, Borneo and Sumatra (Dennis and Aldhous 2004) with 65 species recorded from Pekan, and 47 from North Selangor Peat Swamp Forest (Ng et al 1992(Ng et al , 1994. The Asian arowana (Scleropages formosus) a popular aquarium Wsh occurs in blackwater rivers in the regional peat swamps.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Huet [146], for instance, already mentioned the rearing of the giant goramy in Indonesia as one of the most important freshwater prominent examples [135]. Blackwater swamps, however, are experiencing an alarming rate of land conversion.…”
Section: Aquaculturementioning
confidence: 99%
“…They have been documented as exhibiting extremely high endemicity to swamp forests, up to the point that 33% of known freshwater fish species are associated with peat swamps (Ng et al, 1994;Kottelat et al, 2006). Additionally, Posa et al (2011) found that out of 219 fish species collated from peat swamps, 80 species are restricted to this ecosystem, while 31 species are point endemic species found only in single locations.…”
Section: Aquatic Fauna In Freshwater Swamp Forestsmentioning
confidence: 99%